Discrete-element modelling of the grinding contact length combining the wheel-body structure and the surface-topography models. (November 2016) - Osa, J.L.; Sánchez, J.A.; Ortega, N.; Iordanoff, I.; Charles, J.L.
Abstract: Phenomena governing the grinding process are largely related to the nature and evolution of contact between grinding wheel and ground component. The definition of the contact area plays an essential role in the simulation of grinding temperatures, forces or wear. This paper presents a numerical model that simulates the contact between grinding wheel and workpiece in surface grinding. The model reproduces the granular structure of the grinding wheel by means of the discrete element method. The surface topography is applied on the model surface taking into account the dressing mechanisms and movements of a single-point dresser. The individual contacts between abrasive grits and workpiece are studied regarding the uncut chip thickness, assuming viscoplastic material behaviour. Simulation results are evaluated with experimental measurements of the contact length. The results remark the importance of surface topography and dressing conditions on the contact area, as well as wheel deflection.